Characterization of the hemorrhagic syndrome in the New Zealand white rabbit model following total body irradiation. (3rd December 2021) - Jackson, Isabel L.; Gurung, Ganga; Ayompe, Emmanuel; Fown, Elena-Rose; Triesler, Sarah; Mali, Buddha; Casildo, Andrea; Gibbs, Allison; Poirier, Yannick; Cohen, Eric P.; Newman, Diana; Vujaskovic, Zeljko
Abstract: Purpose: The hemorrhagic syndrome is a major cause of morbidity and mortality associated with the acute radiation syndrome (ARS). We previously characterized the dose–response relationship for total body irradiation (TBI)-induced ARS in the New Zealand White (NZW) rabbit. Thrombocytopenia, hemorrhage, and anemia were strongly associated with morbidity/mortality during the first three weeks post-TBI. The objective of the current study was to further characterize the natural history of thrombocytopenia, hemostatic dysfunction and hemorrhage in the rabbit model at a TBI dose range to induce ARS. Methods: Fifty male NZW rabbits were randomized to receive 7.0 or 7.5 Gy of 6 MV-derived TBI. Sham-irradiated controls ( n = 6) were included as a comparator. Animals were treated with minimal supportive care including pain medication, antibiotics, antipyretics for temperature >104.8 °F, and fluids for signs of dehydration. Animals were culled at pre-determined timepoints post-TBI, or for signs of imminent mortality based on pre-defined euthanasia criteria. Hematology parameters, serum chemistry, viscoelasticity of whole blood, coagulation tests, and coagulation factor activities were measured. A gross exam of vital organs was performed at necropsy. Results: Findings in this study include severe neutropenia during the first week post-TBI followed by thrombocytopenia and severe acute anemia with petechial hemorrhages of the skin and hemorrhage of the vital organs during the second to third weeks post-TBI. Abnormalities in whole blood viscoelastometry were observed concurrent with thrombocytopenia and hemorrhage. Antithrombin activity was significantly elevated in animals after exposure to 7.5 Gy, but not 7.0 Gy TBI. Conclusions: The hemorrhagic syndrome in the rabbit model of TBI recapitulates the pathogenesis described in humans following accidental or deliberate exposures. The rabbit may present an alternative to the rodent model as a small animal species for characterization of the full spectrum of multiorgan injury following TBI and early testing of promising medical countermeasures.